Mueller matrix spectroscopic ellipsometry study of chiral nanocrystalline cellulose films - Mendoza-Galván, Arturo; Muñoz-Pineda, Eloy; Ribeiro, Sidney J. L. [UNESP]; Santos, Moliria V. [UNESP]; Järrendahl, Kenneth; Arwin, Hans (IOP Publishing, 2018)
Chiral nanocrystalline cellulose (NCC) free-standing films were prepared through slow evaporation of aqueous suspensions of cellulose nanocrystals in a nematic chiral liquid crystal phase. Mueller matrix (MM) spectroscopic ellipsometry is used to study the polarization and depolarization properties of the chiral films. In the reflection mode, the MM is similar to the matrices reported for the cuticle of some beetles reflecting near circular left-handed polarized light in the visible range. The polarization properties of light transmitted at normal incidence for different polarization states of incident light are discussed. By using a differential decomposition of the MM, the structural circular birefringence and dichroism of a NCC chiral film are evaluated.
Keywords: biomimetic materials; chiral films; Mueller matrix